2019
DOI: 10.7567/1347-4065/ab29e3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mist chemical vapor deposited aluminum titanium oxide films

Abstract: Aluminum titanium oxide (Al1–xTixOy, an alloy of Al2O3 and TiO2), an attractive high-κ dielectric material, was synthesized by mist chemical vapor deposition, utilizing Al2O3 and TiO2 precursors. X-ray diffraction investigations revealed that the Al1–xTixOy (0 < x < 0.72) films deposited at 400 °C have an amorphous-phase structure. It was found that the bandgap of the Al1–xTixOy films decreases with increasing Ti composition. Moreover, the obtained refractive index, mass density and bandgap of Al2O3 and TiO2 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…E g , and accordingly, the E g increased only by 0.34 eV even though the Y-concentration was ∼40 at%. This tendency is consistent with the ATO results in the previous study [31]. Nonetheless, ∆E c increased by 0.6 eV and ∆E v decreased by 0.26 eV, suggesting that the Fermi level in the YTO layer was lowered by ∼0.3 eV compared to TiO 2 by the acceptor-like effect of Y in TiO 2 .…”
Section: Resultssupporting
confidence: 92%
“…E g , and accordingly, the E g increased only by 0.34 eV even though the Y-concentration was ∼40 at%. This tendency is consistent with the ATO results in the previous study [31]. Nonetheless, ∆E c increased by 0.6 eV and ∆E v decreased by 0.26 eV, suggesting that the Fermi level in the YTO layer was lowered by ∼0.3 eV compared to TiO 2 by the acceptor-like effect of Y in TiO 2 .…”
Section: Resultssupporting
confidence: 92%
“…Applications of high quality mist-CVD prepared Al 2 O 3 in In-Ga-Zn-O thin film transistors 13) and silicon solar cells 15) have already demonstrated. Using mist-CVD, Yatabe et al, recently have reported excellent quality amorphous aluminum oxide films 16,17) whose properties are highly competitive against those prepared with the more sophisticated ALD method. Despite their promising potential as a gate insulator for GaN-based devices, surprisingly however, there have been no reports of AlGaN/GaN MIS-HEMTs using mist-CVD-prepared Al 2 O 3 as gate dielectric, and therefore mist-Al 2 O 3 /AlGaN interfacial qualities remain to be unknown.…”
mentioning
confidence: 99%